2015
DOI: 10.1002/elps.201500022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cell detachment methods on the dielectric properties of adherent and suspension cells

Abstract: Cell analyses such as flow cytometry, dielectrophoresis, and some patch-clamp techniques require that cells be in monodisperse suspension in order for analysis to occur. Where cells have a normally adherent phenotype in vivo, this requires that cells be removed from the surface of the culture flask or vessel. This can be achieved in many ways, but most commonly either by the use of a dissociation medium of some form, or by scraping the cells from the surface. Both methods have potential drawbacks; chemical met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
0
9
0
2
Order By: Relevance
“…Moreover, some cell surface molecules are sensitive to environmental protease activities which are often used for cell dissociation ( emoldonnell and Le andro s i 1 emoldonnell 1 0 art ne - Pomares et al 1998). Specifically, studies across different cell types have revealed that detachment/separation processes affect cell viability, cell membrane properties, and influence cell function (Malorny, Neumann, and Sorg 1981;Batista U 2010;Mahabadi, Labeed, and Hughes 2015;Wachs et al 2003). In this study, we evaluated the impact of different cell detachment methods on the efficiency of cell recovery, viability, phenotype and function.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, some cell surface molecules are sensitive to environmental protease activities which are often used for cell dissociation ( emoldonnell and Le andro s i 1 emoldonnell 1 0 art ne - Pomares et al 1998). Specifically, studies across different cell types have revealed that detachment/separation processes affect cell viability, cell membrane properties, and influence cell function (Malorny, Neumann, and Sorg 1981;Batista U 2010;Mahabadi, Labeed, and Hughes 2015;Wachs et al 2003). In this study, we evaluated the impact of different cell detachment methods on the efficiency of cell recovery, viability, phenotype and function.…”
Section: Discussionmentioning
confidence: 98%
“…Motion of particles tracked across the wells, using an image analysis algorithm on the host PC. Light absorbance is monitored across ten concentric rings inside each well, and the rate of change in light intensity within these rings is determined and scaled to relative area 29,32 . This parameter is proportional to the Clausius-Mossotti factor, a mathematical relationship for the relative polarisability of the suspended particles which is based, in this instance, on the dielectric properties of cytoplasm, membrane and suspending medium and on the applied frequency 14,27 .
Figure 3Schematic of the 3DEP reader platform.
…”
Section: System Descriptionmentioning
confidence: 99%
“…The remaining cells were detached following incubation with Accutase® which has been shown to not significantly alter the DEP properties of the cells. 22 These cells were then centrifuged at room temperature at 259g for 6 minutes. The supernatant was removed and the pellets were resuspended in the previously-described experimental medium.…”
Section: Drug Treatments and Preparationmentioning
confidence: 99%